2011
DOI: 10.1074/jbc.m111.269456
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Protein Pdcd4 Inhibits Translation of p53 mRNA

Abstract: Background: Pdcd4 is a tumor suppressor involved in translational regulation. Results: Pdcd4 interacts with p53 mRNA and inhibits its translation via the 5Ј-UTR. Under stress conditions, the expression of Pdcd4 decreases. Conclusion: Translation of p53 mRNA is suppressed by Pdcd4 under normal growth conditions. Significance: Pdcd4 is a new translational regulator of p53.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 45 publications
(38 reference statements)
6
72
0
1
Order By: Relevance
“…The specific role of PDCD4 in the unwinding of secondary structures via eIF4AI/II was further demonstrated by overexpression of mutant PDCD4, PDCD4-Mut4 (Fig. S1), which contains four amino acid substitutions in two MA3 domains and fails to interact with eIF4AI/II (29). These results showed that both NMD and overall translation levels of Rβ-SL9.7 mRNA were not affected by overexpression of mutant PDCD4 (Fig.…”
Section: Resultssupporting
confidence: 48%
“…The specific role of PDCD4 in the unwinding of secondary structures via eIF4AI/II was further demonstrated by overexpression of mutant PDCD4, PDCD4-Mut4 (Fig. S1), which contains four amino acid substitutions in two MA3 domains and fails to interact with eIF4AI/II (29). These results showed that both NMD and overall translation levels of Rβ-SL9.7 mRNA were not affected by overexpression of mutant PDCD4 (Fig.…”
Section: Resultssupporting
confidence: 48%
“…For RNA isolation from mice livers, a part of the organ was Translational isoforms of p53 in glucose deprivation D Khan et al suspended in TRI reagent (Sigma-Aldrich) and 200-μg/ml glycogen, homogenized by handheld Down's homogenizer (Sigma-Aldrich) by 50 strokes on ice and then manufacturer's protocol was followed as usual. For real-time PCR, first-strand cDNA was synthesized using oligo-(dT) 18 primer (Thermo Scientific) using RevertAid RT enzyme (Thermo Scientific) from 2-μg RNA. Reaction was set up with 2 μl of 1 : 5 diluted cDNA using DyNAmo qPCR kit (Thermo Scientific) that uses SYBR Green chemistry as per manufacturer's instructions on ABI Prism 7900HT machine (Applied Biosystems, Life Technologies) or ABI ViiA7 machine (Applied Biosystems, Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Fourth, PDCD4 is thought to suppress translation of mRNAs containing structured 5'-UTRs by interacting with translation initiation factor EIF4A and inhibiting its helicase activity via its ma3 domains. 38 Here, we have identified ATG5 mRNA but not ATG12 mRNA as a translational The cell viability was determined using ccK8 assay and Lc3 puncta level was detected by immunofluorescence with or without 3-MA treatment as described above. (G-I) skov3 cells were treated with pEGFP-C1 (Mock) or pEGFP-C1-PDCD4 (pPDcD4) plasmids; hepG2 cells were transfected with siRNA targeting PDCD4 (siP) or control (sic) respectively.…”
Section: Discussionmentioning
confidence: 99%